Approximation of functions of two variables by harmonic splines - Klimenko, V. T. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We construct two-dimensional splines and give two versions of an estimate of the deviation of splines from approximated functions. We compare approximations by a planar broken line and by a harmonic spline. We also substantiate the advisability of introduction of the notion of harmonic splines in mathematics.